2009
DOI: 10.1080/00016480802008199
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of edaravone against tobramycin-induced ototoxicity

Abstract: All rats treated only with tobramycin showed a deterioration of hearing. None of the rats given simultaneous treatment with tobramycin and edaravone demonstrated hearing loss. A 7 day delay in edaravone injection still prevented hearing loss, but a 14 day delay had only a temporary prophylactic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Also, various studies show that potential free radical scavengers, such as α-tocopherol (vitamin E) and α-lipoic acid, inhibit gentamicin ototoxicity by neutralizing the free radicals [30,36]. The antioxidant agent, edaravone, which is used particularly in the treatment of acute myocardial infarction, was found effective at inhibiting streptomycin and tobramycin ototoxicity [37,38]. In addition, protection from gentamicin ototoxicity was found in agent M40403, which has a similar efficacy as SOD [39].…”
Section: Discussionmentioning
confidence: 99%
“…Also, various studies show that potential free radical scavengers, such as α-tocopherol (vitamin E) and α-lipoic acid, inhibit gentamicin ototoxicity by neutralizing the free radicals [30,36]. The antioxidant agent, edaravone, which is used particularly in the treatment of acute myocardial infarction, was found effective at inhibiting streptomycin and tobramycin ototoxicity [37,38]. In addition, protection from gentamicin ototoxicity was found in agent M40403, which has a similar efficacy as SOD [39].…”
Section: Discussionmentioning
confidence: 99%
“…Edaravone (MCI-186, 3-methyl-1-phenyl-pyrazolin-5-one) which is clinically used to treat acute cerebral infarction and acute myocardial infarction (Mishina et al, 2005;Tsujita et al, 2004) is a free radical scavenger and can interact with both peroxyl and hydroxyl radicals to form oxidized compounds (Asplund et al, 2009). Edaravone is reported to reduce the amount of oxidative DNA damage and lipid peroxidation in barotraumatic inner ear (Maekawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It can interact with both peroxyl and hydroxyl radicals to form oxidized compounds and thus attenuate ischemic damage [12]. Many studies have revealed that free radical scavengers are also very useful in the treatment of otology disorders, such as inner ear barotrauma, aminoglycoside-induced ototoxicity, and cisplatin-induced ototoxicity [1315].…”
Section: Introductionmentioning
confidence: 99%